Orientación de los entrenadores de balonmano. Influencia del género, edad, experiencia, formación y dedicación semana - Gomez Lopez, B.; Sanchez-Alcaraz Martinez, B. J.; Ruiz Sanchez, V. (Revista Ciencia del Deporte, 2018)
Behaviour adopted by sports coach will facilitate or decrease the degree of satisfaction, motivation, involvement and commitment to practice of sports, thus influencing their sports adherence. The aim of this article will be to know the handball coaches` profile and their differences according to gender, age, years of experience as a player or coach, federative level and the number of hours training. A total of 76 coaches (63 men and 13 women), aged between 16 and 57 years, participated. The Coaches Orientation Questionnaire, validated by Feu et al. (2007). The results showed that, the predominant profiles in handball coaches are dialogue orientation, social climate orientation, team-work orientation and innovation orientation, and the less predominant are the directive orientation and technological orientation. There were no significant differences in coaches` orientation according to their gender and federative level. The analysis of correlations showed that those coaches with more weekly training adopted a more technological orientation. Finally, age, years of coaching experience and weekly training hours did not correlate with any of the coaching orientations.